MATHEMATICAL MODELING OF CHEMICAL-TECHNOLOGICAL PROCESSES, INFORMATION PROCESSING - Turayev Kahramon Nortojiyevich (Web of Journals Publishing, 2024)
The article provides scientific and theoretical information on mathematical modeling of chemical-technological processes, data processing.
Keywords: Modeling, technologies, chemical, method, process, model.